Sewing Training Management at the Permata Job Training Institute Semarang - Fachmi, Aulia Vega; Shofwan, Imam; Gupta, Sachin (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
Training is needed to improve the quality of human resources because it will guarantee that they will become the workers needed by companies or entrepreneurs. This study aims to reveal the management of sewing training at LPK Permata. The research design uses a qualitative approach. Data collection techniques using observation techniques, interviews, and documentation. Research participants included leaders, 2 instructors and 3 trainees. The data validity technique in this research is triangulation of sources and techniques. Data analysis uses data collection, reduction, presentation and drawing conclusions. The results showed that training management includes: (1) planning: identification of needs, formulation of objectives, preparation of programs, preparation of teaching materials, recruitment of instructors and students, determination of methods and media, determination of time and place, determination of evaluation forms, and financing. (2) organizing the organization structure and division of tasks and responsibilities (3) mobilizing based on the form of motivation and implementation of motivation. (4) coaching with montoring. (5) assessment of participants and assessment of activities. (6) development through program improvements and development innovation. It can be concluded that the management of sewing training at LPK Permata has been good in terms of planning, organizing, implementing, and evaluating, but training and development are still lacking. This research provides reference information and references regarding training management for LPK Permata or future researchers.